1999
DOI: 10.1001/archpedi.153.11.1165
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Resident Feedback on Immunization Outcomes

Abstract: To investigate the effect on immunization levels of retrospective written feedback to residents regarding missed immunization opportunities. Design: Randomized trial with control group. Setting: Pediatric resident continuity clinic in an urban hospital-based primary care clinic. Participants: Thirty-two postgraduate level 2 and postgraduate level 3 pediatric residents. Intervention: Monthly retrospective written feedback mailed to residents detailing their missed immunization opportunities and appointment fail… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2003
2003
2017
2017

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(2 citation statements)
references
References 10 publications
0
2
0
Order By: Relevance
“…Tracking systems are computer mechanisms to identify children who have not been seen at a practice recently and/or are not up-to-date on preventive care. 31 As tested via RCT and other rigorous designs (e.g., before-after trials), provider education and feedback have shown inconsistent effects on immunization rates; 56,[76][77][78][79][80] however, when implemented in concert with other strategies as part of a multicomponent intervention, provider education and feedback have been shown to be very effective, improving rates by up to 47 percentage points over 6-month to 2-year periods. 32,34,35,52,53,[81][82][83] Additionally, the "AFIX" (Assessment, Feedback, Incentives, and eXchange of information) framework is an example of a multicomponent provider-based intervention modeled after a program in the state of Georgia that improved pediatric immunization coverage in public clinics from 40% to 91% from 1986 to 2001.…”
Section: Interventions For Providersmentioning
confidence: 99%
“…Tracking systems are computer mechanisms to identify children who have not been seen at a practice recently and/or are not up-to-date on preventive care. 31 As tested via RCT and other rigorous designs (e.g., before-after trials), provider education and feedback have shown inconsistent effects on immunization rates; 56,[76][77][78][79][80] however, when implemented in concert with other strategies as part of a multicomponent intervention, provider education and feedback have been shown to be very effective, improving rates by up to 47 percentage points over 6-month to 2-year periods. 32,34,35,52,53,[81][82][83] Additionally, the "AFIX" (Assessment, Feedback, Incentives, and eXchange of information) framework is an example of a multicomponent provider-based intervention modeled after a program in the state of Georgia that improved pediatric immunization coverage in public clinics from 40% to 91% from 1986 to 2001.…”
Section: Interventions For Providersmentioning
confidence: 99%
“…5 In addition, written retrospective feedback was shown to be ineffective in improving resident's immunization knowledge levels in resident continuity clinics. 6 One instructional method for learning about pediatric immunizations is through patient-based/experiential teaching. At our institution we rely on the clinical interaction with the patients presenting to the resident continuity clinics to provide a large proportion of the instruction experienced during residency.…”
mentioning
confidence: 99%